Determinación de la calidad de suelos, mediante la caracterización físico - químico, biológico para proponer un plan de recuperación de suelos en la comunidad Porotoyacu - Baquero Reyes, Gabriela Nathaly (2015)
On climatic and socio - environmental site, the maximum and minimum temperature, rainfall in the area and the cloud cover was analyzed, also through surveys social information was compiled, economic and environmental development of the habitants of the Community. It is noted that the area is tropical humid with rainfall exceeding 4000 mm annually with temperatures ranging between 18 and 30 ° C, which characterizes a very distinct climate and striking the soil formation, as high humidity and temperature causes decomposition processes are accelerated, Cannot be adhered structure and especially nitrites down so the leaching and washing of organic matter is immediate. Once established the study areas of soil composite samples were analyzed for physical, chemical and biological aspect, in its own biota species of bacteria, pathogenic and antagonistic fungi were collected; which it is part of the dynamics of the soil and must be handled with agronomic practices; the soil horizon lacks the horizon with abundant organic matter, thereby leaching processes are frequent, with horizons that is limited in thickness no more than 17 centimeters in the good places, the horizon B and C ranging so soon and with small thickness, the water table is very close, in some cases the C horizon or bedrock does not appear; Porotoyacu soils are very fragile. Then based on the results obtained in the field research and lab work a recovery plan Soil that is based on permanent programs (agricultural amendments, construction of works to improve the productive capacity of the soil) and Special Plans was established (afforestation and reforestation, protection of native forests)